If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + -1y + -1y + y = 11 Combine like terms: 2y + -1y = 1y 1y + -1y + y = 11 Combine like terms: 1y + -1y = 0 0 + y = 11 y = 11 Solving y = 11 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 11
| 151=-x+7(-6x+3) | | 28=3+8(z-7) | | 3(12)=a(a+5) | | -151=-x+6(-6x+3) | | 2X+3=(X+5)*(X+5) | | 11q-7q=20 | | -20y+1=2-16y+11 | | 10.66+y=28.66 | | 3x-1=(X+5)*(X+5) | | 3x-21=9x+54 | | -5-8(1-3k)=19 | | 13p=-36 | | x^2+5x=3x+24 | | x^2-4.07x+2.71=0 | | (x+3)(x-7)(x+8)=0 | | 10.66+7=28.66 | | 9m-4m=15 | | f(0.75)=2(0.75)+4 | | 5b+3b=8 | | (4z-1)2= | | 0=5x^4-90x^2 | | 2x-3-6x-4=5 | | (x+1)(x+2)=11+(x)(x) | | 0.55555x-4=2+x-18 | | x^2+3x-147=0 | | 5f+3=29 | | 72-12y+y=5 | | 3x+2x-15= | | x^2+3-147=0 | | 3/4b=6 | | 17.17+w=28.78 | | 2x+12=3x-7 |